Teachers’ Practices in Promoting Cross Cultural Values through English Language Teaching - Ray Suryadi; Syarifuddin Dollah; Samtidar; Alifiah Pratiwi; Sultan; La Ode Idrus Hamid Basri; Syamsinar (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates how English teachers promote cross cultural values by examining the strategies they use, their understanding of cross-cultural concepts, and the challenges they encounter. Using a qualitative descriptive design, data were gathered through interviews and classroom observations. The findings show that teachers integrate cross cultural values mainly through comparative discussions, the use of authentic cultural materials, and reflective tasks that guide students to recognize cultural similarities and differences. Although teachers acknowledge the importance of cross-cultural awareness, their conceptual understanding is still limited and varies based on professional experience and training. The study also identifies several challenges, including the lack of culturally rich resources, limited institutional support, and concerns about addressing culturally sensitive issues in the classroom. Overall, the results highlight that teachers contribute meaningfully to cross cultural learning but require stronger pedagogical support and more structured guidance to integrate these values effectively in English language teaching.